(untitled) (Private Law, 2021)
Purposes of this work are to know and to analyse legal consequences of â€œghaibâ€ divorce (a divorce which conducted against uncontacable husband/wife) in the view of Islamic law and law on marriage in the Verdict Number 130/Pdt.G/2013/PA.MTR. applied method of this work is normative legal research. Judgeâ€™s consideration in the Verdict Number 130/Pdt.G/2013/PA.MTR based on laws and facts has been fulfill the divorce requirements as regulated in the Explanation of Article 19 letter (f) Government Regulation Number 9 of 1975 and Article 116 letter f Islamic Compilation Law. Therefore, in this judgeâ€™s verdict it imposing First Talaq Baâ€™in Shugraa of the applicant to defendant. Legal consequences of uncontactable husband divorce according to Islamic Compilation Law it can be articulate as first talaq baâ€™in shugraa. However, in the Marriage Law this term is unknown, thus its legal consequences had the same effect as regular divorce.